2000
DOI: 10.1074/jbc.m002597200
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of TOGp with Microtubules and Tubulin

Abstract: TOGp is the human homolog of XMAP215, a Xenopus microtubule-associated protein that promotes rapid microtubule assembly at plus ends. These proteins are thought to be critical for microtubule assembly and/or mitotic spindle formation. To understand how TOGp interacts with the microtubule lattice, we cloned fulllength TOGp and various truncations for expression in a reticulocyte lysate system. Based on microtubule co-pelleting assays, the microtubule binding domain is contained within a basic 600-amino acid reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 59 publications
7
78
0
Order By: Relevance
“…In this study, we have shown that PRIC285, which has an UvrD helicase-like domain in its C-terminal region (amino acids 1584-1991), acts as a nuclear receptor coactivator and interacts with other nuclear receptors. We have also found that TOG, a microtubule-and tubulininteracting protein (46), also interacts with PPAR␣ in the GST pull-down assays (unpublished data), which is consistent with the presence of five LXXLL motifs in this protein (31). Further studies are needed to ascertain the coactivator functions of these newly identified proteins in PRIC complex that contain the LXXLL motif necessary for the interaction with nuclear receptors (16).…”
Section: Discussionmentioning
confidence: 65%
“…In this study, we have shown that PRIC285, which has an UvrD helicase-like domain in its C-terminal region (amino acids 1584-1991), acts as a nuclear receptor coactivator and interacts with other nuclear receptors. We have also found that TOG, a microtubule-and tubulininteracting protein (46), also interacts with PPAR␣ in the GST pull-down assays (unpublished data), which is consistent with the presence of five LXXLL motifs in this protein (31). Further studies are needed to ascertain the coactivator functions of these newly identified proteins in PRIC complex that contain the LXXLL motif necessary for the interaction with nuclear receptors (16).…”
Section: Discussionmentioning
confidence: 65%
“…Western blots were also used to verify that the subtilisin treatment fully removed the C-terminal tails from both ␣-and ␤-tubulin (supplemental Fig. S3) (35)(36)(37).…”
Section: Methodsmentioning
confidence: 99%
“…TOG has been identified as a microtubule binding protein (Spittle et al, 2000). The association of TOG2 with the CSK in neural cells was investigated by cell fractionation.…”
Section: Subcellular Distribution Of Tog2 In Oligodendrocytes and Neumentioning
confidence: 99%
“…The microtubule binding activity is contained within the N-terminal half of the protein (residues 368 -910), whereas the C-terminal half of the protein contains tubulin dimer binding activity (Spittle et al, 2000). A model has been proposed whereby TOG mediates polar elongation of microtubules by binding to the plus end of the microtubule and discharging a tubulin dimer (Spittle et al, 2000).…”
Section: Introductionmentioning
confidence: 99%